Second Annual Meeting of the Invasive Bacterial Diseases Surveillance Network in Europe: meeting report - European Center for Disease Control and Prevention (2013)
Paula Lavado é representante de Portugal neste projecto participando nas reuniões científicas e enviando os dados de Portugal